2001
DOI: 10.1097/00007890-200106150-00024
|View full text |Cite
|
Sign up to set email alerts
|

Xenogeneic Extracellular Matrix Grafts Elicit a Th2-Restricted Immune Response1

Abstract: Porcine extracellular matrix elicits an immune response that is predominately Th2-like, consistent with a remodeling reaction rather than rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
303
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 354 publications
(333 citation statements)
references
References 25 publications
22
303
0
8
Order By: Relevance
“…Donor-derived MHC class I, which immunolocalized preferentially to donor endothelial cells, became undetectable during decellularization, but was again measurable in the host blood vessels following implantation (host-derived MHC class I), in agreement with previous studies that have demonstrated evasion of rejection when the donor is vascularized by host blood vessels (48,49). As well as a shift toward an M2-like phenotype with decellularization, we have also observed a shift away from a TH1 (as in classical acute rejection, for example) toward a TH2-like phenotype (generally associated with transplant acceptance), in agreement with previous studies (32,50,51).…”
Section: -47)supporting
confidence: 92%
“…Donor-derived MHC class I, which immunolocalized preferentially to donor endothelial cells, became undetectable during decellularization, but was again measurable in the host blood vessels following implantation (host-derived MHC class I), in agreement with previous studies that have demonstrated evasion of rejection when the donor is vascularized by host blood vessels (48,49). As well as a shift toward an M2-like phenotype with decellularization, we have also observed a shift away from a TH1 (as in classical acute rejection, for example) toward a TH2-like phenotype (generally associated with transplant acceptance), in agreement with previous studies (32,50,51).…”
Section: -47)supporting
confidence: 92%
“…S1) and systemically (50), promote a local microenvironmental niche that facilitates stem cell recruitment and/or maintenance (51-53). An independent contributing factor to the host response is the effect of ECM scaffolds on tissue macrophages (33,(54)(55)(56) and T cells (57). Macrophages are critical determinants of the overall regenerative response in vivo (56).…”
Section: Discussionmentioning
confidence: 99%
“…are relatively well conserved across mammalian species and, therefore, do not evoke adverse immune reaction. 25,26 However, a number of recent studies have shown that cellular components may remain after decellularization in a number of ECM materials, even those that have received approval for clinical use. 27 Further studies have suggested that inefficient removal of cellular contents such as DNA and the a-gal epitope during decellularization may be responsible for inflammation and poor outcomes after implantation.…”
mentioning
confidence: 99%